Financial Inclusion and Laku Pandai Program on Individual Bank Profitability: Case Study in Indonesia - Ruth Margaretha Setiawan; Chaikal Nuryakin (Green Publisher Indonesia, 2026)
This study attempts to investigate the effect of the level of financial inclusion and the Laku Pandai program on individual bank profitability. Because from the bank's point of view, profitability is needed for business continuity. This study uses a financial inclusion index with a macro approach where there are three dimensions considered, namely penetration, availability, and usage, which will be processed using two-stage PCA. There are 31 banks that joined Laku Pandai, and all of them will be included in the sample using the Fixed Effect model. The period used in the research is from the initial implementation year of the Laku Pandai program (2015) to 2021. The results of the research show that the effect of financial inclusion on individual bank profitability has yet to be proven. Apart from that, the difference in the implementation of the Laku Pandai program in the control and treatment groups did not produce a significant difference in ROA in this dataset but resulted in a significant negative difference in ROE. Therefore, the authorities need to review the financial inclusion program through banks (bank-based). The behavior of underbanked and unbanked populations' financial transactions may not be in accordance with the banking business model.